Environmental footprint of a colonoscopy procedure: Life cycle assessment - Lämmer, Paulina; Oomkens, Dorien; Stobernack, Tim; Duijvestein, Marjolijn (Endoscopy International Open, 2025)
Gastroenterology is a specialty that has evolved rapidly over time, especially in terms of advancements in endoscopic procedures. However, these advancements also present challenges, given the substantial resource demands associated with endoscopy procedures. Numerous actions could be taken to develop a resilient healthcare system that consumes as few resources as possible, but recommendations are needed to prioritize which processes could be improved. We aimed to evaluate the environmental footprint of a colonoscopy procedure, and to identify the main contributing impact process categories.A single-center observational study was conducted at a Dutch university hospital. No clinical patient data were collected, but the colonoscopy procedure was studied. Data were collected during 13 colonoscopies. Life cycle assessment (LCA) was used to calculate environmental impact.Damage to human health from one colonoscopy was 11.3·10–5 disability-adjusted life-years, equivalent to 1 hour. A single colonoscopy resulted in emission of 56.4 kg of CO2-equivalent (CO2eq), equal to driving a car for 255 km or 55 days of emissions for an average European household. Transportation of patients and staff (76.5%) and disposables (13.5%) were the greatest contributors to damage to human health.Among the 13 colonoscopies studied, the environmental impact was mainly attributable to transportation of patients and staff, and disposables. Therefore, raising awareness about the impact of transportation by car, and reducing resource consumption, particularly of disposable products, should be prioritized. Implementing alternatives to colonoscopy, such as intestinal ultrasound, could reduce the environmental footprint of the healthcare system.
Keywords: Endoscopy Lower GI Tract; Inflammatory bowel disease; Polyps / adenomas / ...